Pulmonary sclerosing pneumocytoma demonstrating intratumoral hematoma. (2019) - Lee, Ko; Sasaki, Mamoru; Kakimoto, Tomoo; Morinaga, Shojiroh; Yamamoto, Tatsuya; Iwamaru, Arifumi; Ogata, Kentaro; Minematsu, Naoto
Abstract: Pulmonary sclerosing pneumocytoma (PSP) is a rare benign neoplasm of the lung that shows a slow growing pattern. Corresponding contrast-enhancements on chest computed tomography (CT) vary widely in both patterns and degrees. However, gross intratumoral radiolucencies, attributable to cyst formation, necrosis, or intratumoral hematoma, were rarely reported in PSP cases. We herein report on a case involving a 61-year-old Japanese women with PSP demonstrating CT-defined intratumoral radiolucency. A chest CT scan revealed a solitary and well-circumscribed nodule that showed a substantial growth over a 7-year period. The tumor was composed of a solid portion visualized with contrast-enhancement and a central radiolucency on a chest CT scan. A positron emission tomography scan revealed high uptake of fluorodeoxyglucose on the solid portion of the tumor, but the radiolucent portion showed negative uptake. The examination of a tumor specimen obtained by a percutaneous core needle biopsy aided in determining a pathological diagnosis of PSP, and the patient subsequently received a right lower lobectomy of the lung. The portion of central radiolucency on the CT scan corresponding to the surgical specimen was pathologically proven to be gross hematoma.